Ileal transposition rapidly improves glucose tolerance and gradually improves insulin resistance in non-obese type 2 diabetic rats. (24th July 2018) - Zhu, Hengliang; Wang, Huaiming; Zheng, Zhihai; Ye, Bailiang; Ruan, Xiaojiao; Zheng, Xiaofeng; Li, Guoxin
Abstract: Background: Many studies have confirmed that ileal transposition can improve type 2 diabetes mellitus (T2DM), accompanied by increased glucagon-like peptide-1 (GLP-1). We performed the experiment on diabetic rats to evaluate the effects and mechanisms of ileal transposition on the glycemic metabolism. Methods: Twenty Goto-Kakizaki (GK) rats were randomly divided into the ileal transposition group (IT group) and the sham operation group (Sham group). Weight, food intake, fasting plasma glucose (FPG), fasting insulin (F-ins), oral glucose tolerance test (OGTT) and GLP-1 were determined at baseline and 1, 4, 8, 16 and 24 weeks post-operatively. The homeostasis model assessment-insulin resistance (HOMA-IR) index and the area under the curve (AUC) during OGTT were measured. Histological determination of the GLP-1 receptor (GLP-1R) was performed on the pancreas and ileum 24 weeks post-operatively. Results: In comparison with the Sham group, the IT group showed a higher GLP-1 level and lower AUC at 4, 8, 16 and 24 weeks post-operatively (all P  < 0.05) and a lower FPG, F-ins levels and HOMA-IR at 8, 16 and 24 weeks post-operatively (all P  < 0.05). Compared with baseline levels, the plasma GLP-1, AUC and FPG levels decreased significantly at each post-operative time point in the IT group (all P  < 0.05), but not in the Sham group (all P  > 0.05); F-ins and HOMA-IR significantly decreased at 8, 16 and 24 weeks post-operatively in the IT group (all P  < 0.05). GLP-1R expression in the IT group was significantly higher than that of the Sham group in both the pancreas and the ileum at 24 weeks post-operatively ( P  < 0.05). Conclusions: Ileal transposition ameliorated glucose metabolism without reduction in weight or food intake in GK rats, which may be induced by the increased GLP-1 expression. However, the delayed improvement of insulin resistance, accompanied by decreased plasma insulin levels, might not directly result from the increased GLP-1.